Protective discrimination and development of scheduled castes: An alternative model for good governance - Bhargava, B.S.; Samal, Avinash (1998)
Following a brief outlining of issue, current importance, genesis and logic of the reservation policy, the authors attempt an objective analysis of the policy to ascertain its implications and impact an socio-economic upliftment of the targeted section of population. Using the term `protective discrimination' interchangibly with reservation policy, they present an alternative model specifyingly suggesting how to follow the policy and to whom its benefits be channelised. - Reproduced
Keywords: Scheduled caste; Good governance - India; Backward classes - India; Backward classes